Pengaruh Kualitas Pelayanan, Suasana Tempat, Dan Harga Terhadap Kepuasan Konsumen Pada Restoran Popolamama Di Tangerang - Ardianingrum, Denysa Ratna; As Ad, Muhammad (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to determine the influence of Service Quality, Place Atmosphere and Price on Consumer Satisfaction at the Popolamama Restaurant in Tangerang simultaneously or partially. The data used is primary data collected through distributing questionnaires to 100 respondents who had visited the Popolamama restaurant. The quantitative method and results of this research are based on respondents' answers using a Likert scale. The analytical method used in this research is multiple linear regression test, F test, t test and coefficient of determination. The results of this research show that using the F test (simultaneous) there is a significant influence between service quality, atmosphere and price on consumer satisfaction. The t test (partial) shows that service quality has no influence on customer satisfaction, the atmosphere of the place has a significant influence on customer satisfaction, and price has a significant influence on customer satisfaction.